Pemodelan dan Simulasi Protokol Routing DSR pada Jaringan Vehicular Ad hoc Network (VANET) Di Pekanbaru - Azmi, Agusurio; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pekanbaru city is a large area, therefore traffic congestion often occurs due to the density of society’s vehicles. From this problem, it is needed a technology that can exchange information between vehicles. Information Technology that can involve many vehicles with special network types without dependence on an infrastructure is Ad Hoc Network. One type of this network is Vehicular Ad Hoc Network (VANET). VANET is a new concept in enabling communication between Vehicle to Vehicle (V2V). For efficient data packet delivery, VANET requires a routing protocol. In this research, for simulated and analyzed performance is used the Dynamic Source Routing (DSR) protocol. NS-2 is used to simulated a moved nodes, SUMO software is used to simulated real map of SKA Mall crossroad and parameter the quality of performance routing protocol DSR can determined by Packet Delivery Ratio (PDR). This simulation uses scenario 100 nodes, 150 nodes, 200 nodes and 250 nodes. The result shows that the VANET designed can work well with average of the PDR is 99.61%.Keywords : VANET, DSR, Routing Protocol